2015
DOI: 10.1111/jdi.12424
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic pathology of islet endocrine cells in type 2 diabetes: β‐Cell growth, death, regeneration and their clinical implications

Abstract: Diabetes is defined as a disease of hyperglycemic metabolic disorder caused by impaired insulin action or low insulin secretion, resulting in the occurrence of vascular complications. Based on this definition, diabetes therapy has long been oriented to correct hyperglycemia against the specific complications of diabetes. This definition has posed some difficulties, however, in understanding of the pathophysiology of this complicated disease and as such in the establishment of an effective treatment. With conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 66 publications
1
44
1
Order By: Relevance
“…Loss of pancreatic β-cells due to Cd-induced apoptosis may thus be another mechanism for effects of Cd exposure on pre-diabetic risk. Yagihashi et al (2016) reported a reduction in pancreatic β-cell volume density in both a diabetic, obese American group and diabetic, lean Asian (Japanese and Korean) groups, but compensatory hyperplasia of pancreatic β-cells has been evident only in the diabetic, obese American group. These observations may explain lower mortality among diabetic obese people, compared with diabetic lean persons (Engelmann et al 2016).…”
Section: Cadmium and Diabetic Riskmentioning
confidence: 99%
“…Loss of pancreatic β-cells due to Cd-induced apoptosis may thus be another mechanism for effects of Cd exposure on pre-diabetic risk. Yagihashi et al (2016) reported a reduction in pancreatic β-cell volume density in both a diabetic, obese American group and diabetic, lean Asian (Japanese and Korean) groups, but compensatory hyperplasia of pancreatic β-cells has been evident only in the diabetic, obese American group. These observations may explain lower mortality among diabetic obese people, compared with diabetic lean persons (Engelmann et al 2016).…”
Section: Cadmium and Diabetic Riskmentioning
confidence: 99%
“…Several studies report that the mass and volume of b-cells are reduced by about 30 to 60% in type 2 diabetic patients, thus creating the generalized consensus on the central role of the b-cell functional decline in the onset of T2DM. 15,16 Pathological modifications of the b-cell epigenome can cause b-cell insufficiency by impairing the maintenance of the differentiated, functional state of these cells. 17 Indeed, there are master genes responsible for the differentiation of pancreatic a-and b-cells, and epigenetic mechanisms can alter the physiologic and balanced differentiation of the common precursor cells, both during developmental stages and adult life.…”
Section: B-cell Development and Functionmentioning
confidence: 99%
“…Compared with non-diabetic autopsy cases, β-cell volume density in Korean people with T2D was found to be 40% lower, 33 similar to that in Japanese people with T2D. 34 Although we measured pancreatic volume and not β-cell mass in this study, there is solid evidence supporting a positive association between pancreatic volume and glucose homeostasis. 16,35,36 Occupancy of β cells in the pancreatic parenchyma is known to reach the adult level at the age of 5-10 years.…”
Section: Discussionmentioning
confidence: 61%
“…There is much evidence to show that pancreatic β‐cell volume is crucial in glucose homeostasis. Compared with non‐diabetic autopsy cases, β‐cell volume density in Korean people with T2D was found to be 40% lower, similar to that in Japanese people with T2D . Although we measured pancreatic volume and not β‐cell mass in this study, there is solid evidence supporting a positive association between pancreatic volume and glucose homeostasis .…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation